Synthetic fertilizers and vermicompost in juvenile Persian lime (Citrus x latifolia Tanaka ex Q. Jiménez) trees: PERSIAN LEMON (Agro Productividad, 2023)
Objective: To evaluate fertilization with vermicompost and NPK mineral fertilizer in young Persian lime (Citrus x latifolia Tanaka ex Q. Jiménez) trees.Design/Methodology/Approach: A randomized block design was established with eight treatments and four repetitions: T1, 0 kg tree-1; T2, 90-22.5-22.5 N-P-K kg ha-1; T3, 2 kg tree-1 of vermicompost; T4, 3 kg tree-1 of vermicompost; T5, 4 kg tree-1 of vermicompost; T6, 90-22.5-22.5 N-P-K kg ha-1 + 2 kg tree-1 of vermicompost; T7, 90-22.5-22.5 N-P-K kg ha-1 + 3 kg tree-1 of vermicompost; and T8, 90-22.5-22.5 N-P-K kg ha-1 + 4 kg tree-1 of vermicompost. The study variables were tree height, stem thickness, crown diameter from North to South (N-S) and East to West (E-W), soil pH, and soil moisture (%). The data were statistically analyzed applying the MINITAB V.17 statistic through an ANOVA (P≤0.05), while a multivariate analysis was used for the means comparison.Results: The tree height and crown diameter variables had different results in the Persian lime trees treated with 4 kg tree-1 of vermicompost (T5). The tree canopy had a similar development than T5 with vermicompost treatments combined with NPK mineral fertilizer.Study Limitations/Implications: Conventional lime production indiscriminately uses synthetic fertilizers, polluting natural resources. Organic fertilizers are a nutritional alternative for the trees.Findings/Conclusions: The vermicompost treatment efficiently maintains adequate soil moisture during the dry season, improving the growth and development of Persian lime trees.